Powdery mildew and rust fungi of “Bugskiy Gard” National Nature Park (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Mycological research in the territory of Bugskiy Gard National Natural Park (Mykolaiv region, Ukraine) resulted in the detection of 64 species of obligate phytotrophic fungi of the orders Erysiphales (33 species) and Pucciniales (31 species). Fungi belonging to species Erysiphe prunastri, Phragmidium violaceum, Puccinia annularis, P. glechomatis and P. permixta are reported for the first time in the territory of Right Bank Steppe of Ukraine. Identified fungi parasitized 86 species of host plants belonging to 70 genera and 26 families. The list of the recorded fungi and their hosts is given in the article.
Keywords: powdery mildew, rust, fungi, plants, Bugskiy Gard National Nature Park.